Modern Security Dilemma: A Space Security Perspective for the Future World - Moniruzzaman (HISTORICAL: Journal of History and Social Sciences, 2025)
In an increasingly interconnected and technologically advanced world, the domain of space has emerged as a critical frontier for both national security and international cooperation (Johnson, 2019). However, as nations expand their presence in space, the risks and challenges associated with ensuring security in this domain have become more pronounced (Fountain, 2020). This research article examines the modern security dilemma through the lens of space security, exploring the complexities, tensions, and opportunities that arise as states navigate the dual imperatives of safeguarding their interests while promoting stability and cooperation in outer space (Weeden & Sampson, 2021). By analyzing current trends, emerging threats, and potential pathways for collaboration, this article seeks to provide insights and recommendations for addressing the space security dilemma in the future world.